Social identity and environmental citizenship in multinational corporations: an exploratory investigation and future research directions. (3rd September 2018) - Lasrado, Flevy; Arora, Bimal
ABSTRACT: Adapting to a 'green' agenda requires active engagement of all relevant stakeholders such as societies, national, international and multinational corporations. Within organizations, leaders need to create a conducive organizational culture and identity to inculcate prosocial behaviours for becoming environmentally sensitive and responsible among employees through environmental citizenship. It can be argued that environmental citizenship among employees can enhance an organization's environmental performance and impacts. Linking the notions and theories of social identity and environmental citizenship, this exploratory study examines the perceptions, attitudes and values of managers on engaging employees in green involvement. We also explore the organizational factors that were implemented across the workplace and its underpinning sustainable strategies for green engagement with an overarching research question: How can organizations promote green behaviour and identity among employees and engage them in meeting green targets for organizations? We employed a qualitative method by designing a focus group study. Our findings help us explore factors for promoting a social identity and environmental citizenship in business organizations and to understand speciﬁc methods that motivate green behaviours among employees, so that a culture and identity of being green becomes prominent and extends to the homes and wider society of employees.